English Teachers’ Strategies in Creating Formative Test Questions in a Public High School - Irna Aswanti Ibrahim; Amirullah Abduh; Chairil Anwar Korompot (Naifaderu Cipta Sejahtera, 2023)
Purpose This research is about the strategies are used and challenges faced by English teachers in creating formative test questions. In this research, there are two research questions were proposed, namely: 1) What are the strategies used by English teachers at SMA Negeri 1 Takalar in creating formative test questions? 2) What are the challenges encountered by English teachers at SMA Negeri 1 Takalar in creating formative test questions? Methodology The method used in this research was the qualitative descriptive method. This study involved two English teachers at SMA Negeri 1 Takalar. Results/Findings The results of this study indicate there are some types of strategies are used by English teachers at SMA Negeri 1 Takalar in creating formative test questions, namely: a) The English teacher contacting the other English teachers; b) Discussing with the other English teachers; c) Analyzing the results of the discussion; d) Drawing conclusions; e) Reading or understanding the basic competence of the material; f) Reading a lot of references; g) Creating the questions based on the basic competence; h) Conducting content validity; i) Using students’ knowledge; and j) Using level of difficulty. Meanwhile, for the challenges are encountered by the teachers in creating formative test questions, there are some types of challenges, namely: a) The difficulty in selecting of words; b) The difficulty to know the level of students’ knowledge and measuring students’ ability; and c) The lack of facilities. Implications This research offers some implications for the other teachers because this research can help many people, in this case teacher in creating formative test questions. Through this research, other teachers can know what the strategies used and the challenges encountered by English teacher in creating formative test questions.